An investigation of spiritual coping strategies among mothers of children with autism in Indonesia - Gimanda Nahdiah Diana; Cesa Septiana Pratiwi; Iwan Setiawan (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2026)
Background: Autism spectrum disorder places substantial emotional, social, and psychological demands on mothers, who often serve as the primary caregivers. In Indonesia, spirituality and religious practice are closely intertwined with everyday life and may function as important coping resources when mothers face prolonged caregiving stress, stigma, and uncertainty about their children’s future. Objective: This study explored how mothers of children with autism in Indonesia integrate spirituality into their coping processes during everyday caregiving. Methods: A qualitative descriptive study was conducted. Ten mothers of children diagnosed with autism spectrum disorder were recruited purposively on the basis of their role as primary caregivers and their involvement in spiritual or religious practices. Data were collected through in-depth semistructured interviews conducted face-to-face or online. Each interview lasted approximately 60–90 minutes, was audio-recorded with consent, transcribed verbatim, and analyzed thematically with the support of NVivo software. Results: Five main themes were identified: (1) the search for and meaning of spirituality, (2) emotional responses and the dynamics of acceptance, (3) spiritual coping strategies and daily practices, (4) culture, stigma, and social support, and (5) self-transformation and reflections on parenting. These findings suggest that faith actively shapes mothers’ resilience, hope, and acceptance of their circumstances. Conclusions: Spiritual coping is a crucial element that supports the psychological well-being of mothers caring for children with autism. The findings support the incorporation of spirituality-based approaches into mentoring and support practices for healthcare professionals, educators, and families as part of a holistic strategy for assisting mothers of children with autism.